2010
DOI: 10.4236/jwarp.2010.211117
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Copper Ions from Acid Mine Drainage Wastewater Using Ion Exchange Technique: Factorial Design Analysis

Abstract: A factorial experimental design method was used to examine the "Cu 2+ " removal from acid mine drainage wastewater by ion exchange technique. Ion Exchange technique is preferred because of reduced sludge generation compared to conventional treatment techniques and better decontamination efficiency from highly diluted solutions. Factorial design of experiments is employed to study the effect of four factors pH (3, 5, and 6), flow rate (5, 10, 15 L/hr), resin bed height (20, 40 and 60 cm) and initial concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A comparison with other adsorbents indicated a high metal ion adsorption capacity of nano kaolinite extracted and prepared from deposits of Sweileh sand, west Amman, Jordan. Findings revealed that nano kaolinite offered promising adsorption efficiency versus various other adsorbents reported for metal ions adsorption and nano kaolinite could possibly be used for the adsorption of heavy metal ions from industrial effluents (Bulgariu et al, 2019;Chen et al, 2019;Gaikwad et al, 2010;Godiya et al, 2019a;Godiya et al, 2019b;Ibrahim and Fakhre, 2019;Jiang et al, 2019;Kausar et al, 2018a;Kausar et al, 2018b;Khera et al, 2019;Liang et al, 2013;Mousavi et al, 2019;Nadeem et al, 2016;Sandoval et al, 2019;Zafar et al, 2018;Zhao et al, 2019).…”
Section: Comparison Of Nano Kaolinite With Other Adsorbentsmentioning
confidence: 99%
“…A comparison with other adsorbents indicated a high metal ion adsorption capacity of nano kaolinite extracted and prepared from deposits of Sweileh sand, west Amman, Jordan. Findings revealed that nano kaolinite offered promising adsorption efficiency versus various other adsorbents reported for metal ions adsorption and nano kaolinite could possibly be used for the adsorption of heavy metal ions from industrial effluents (Bulgariu et al, 2019;Chen et al, 2019;Gaikwad et al, 2010;Godiya et al, 2019a;Godiya et al, 2019b;Ibrahim and Fakhre, 2019;Jiang et al, 2019;Kausar et al, 2018a;Kausar et al, 2018b;Khera et al, 2019;Liang et al, 2013;Mousavi et al, 2019;Nadeem et al, 2016;Sandoval et al, 2019;Zafar et al, 2018;Zhao et al, 2019).…”
Section: Comparison Of Nano Kaolinite With Other Adsorbentsmentioning
confidence: 99%
“…Conventional methods for removing metals from industrial effluents include chemical precipitation, coagulation, solvent extraction, electrolysis, membrane separation (Gürel et al 2005), ion -exchange (Roque-Malherbe et al 2007;Barbooti, 2010;Gaikwad et al, 2010) and adsorption on different materials (El Harti et al, 2013ab;Al-Jlil, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide range of AMD treatment systems have been developed based on chemical, physical and biological processes, alone or in combination, with systems generally categorised as either “passive” or “active” depending on the process [ 2 , 4 , 16 , 17 ]. Examples of processes are: pH control or precipitation, adsorption or absorption, electrochemical concentration, flocculation/filtration/settling, biological mediation, redox control (sulphate reduction), ion exchange and crystallisation [ 2 , 17 , 18 , 19 ]. The main difference between these treatment systems is their ability in handling the acidity, flow rate and acidity load (i.e., the product of acidity and flow rate) of the influent AMD [2] .…”
Section: Introductionmentioning
confidence: 99%